165 Effect of feed forms on physical characteristics of eggs in the duration of storage. (7th December 2018) - Oludoyi, I; Ogunwole, O; Adeyemo, G; Babayemi, O
Abstract: Mash is the commonest feed form given to chickens in Nigeria. However, other forms (pellet-crumbs, pellet, crumble) in which they are fed to laying chickens may have substantial impacts on nutrients delivery and ultimately the eggs obtained from the hens. Hence, this study was aimed at investigating the effects of feed form on physical characteristics of egg in the duration of storage. Lohman Brown layers (n=360) aged 23 weeks were randomly allotted to four isonitrogenous and isocaloric feed forms (mash, pellet, crumble, and pellet-crumble). Each treatment was replicated ten times with nine birds each. At 39 week, 280 eggs were sampled and stored at ambient temperature which ranged from 24.1–28.9 oC and relative humidity of 73–84%. External and internal physical characteristics were determined at days 0, 7, 14, 21 and 28 of egg storage. The experiment was a 4x5 factorial arrangement in a completely randomized design. Aside the yolk colour, egg weight loss, length, width, shape index and all the internal characteristics were not significantly (P>0.05) influenced by feed forms. Weight of eggs collected from birds fed pellet-crumble was significantly (P < 0.05) higher (65.86g) compared with mash (62.62g) and crumble (62.02g) while those on pellet (64.29g) were not different from the other forms. Similarly, egg width (45.83mm) and shell weight (6.98g) of birds fed pellet-crumble were higher among the group. Albumen height, haugh unit, yolk height and index reduced with increasing storage days. Egg width, shell and albumen weight were not significantly (P>0.05) affected by storage days. Effects of interaction on feed form and storage days on shell thickness and yolk colour differed significantly (P < 0.05). Hens on pellet and mash had higher shell thickness on day 0 compared with other storage days. In conclusion, feed forms influenced the external egg characteristics in duration of storage.